2020
DOI: 10.3390/medicina56090482
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Analysis of Actinic Keratosis before and after Topical Treatment Using a Cold Stimulation and Near-Infrared Spectroscopy

Abstract: Background and objectives: The possible evolution of actinic keratoses (AKs) into invasive squamous cell carcinomas (SCC) makes their treatment and monitoring essential. AKs are typically monitored before and after treatment only through a visual analysis, lacking a quantitative measure to determine treatment effectiveness. Near-infrared spectroscopy (NIRS) is a non-invasive measure of the relative change of oxy-hemoglobin and deoxy-hemoglobin (O2Hb and HHb) in tissues. The aim of our study is to determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Another innovative aspect of our project was the use of NIRS, a non-invasive technique that evaluates hemoglobin relative concentration variations, for the assessment of the response to treatment. The feasibility of this method for the AK monitoring has already been demonstrated in previous studies conducted by our group ( 20 , 21 ), in which we identified through a multivariate analysis of variance a different vascular response in AK compared to healthy skin and in the lesions themselves before and after treatment with Imiquimod 3.75%. In the present study, however, despite the evidence of clinical response to treatment, we did not find significant differences for O 2 Hb and HHb signals in the two periods.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Another innovative aspect of our project was the use of NIRS, a non-invasive technique that evaluates hemoglobin relative concentration variations, for the assessment of the response to treatment. The feasibility of this method for the AK monitoring has already been demonstrated in previous studies conducted by our group ( 20 , 21 ), in which we identified through a multivariate analysis of variance a different vascular response in AK compared to healthy skin and in the lesions themselves before and after treatment with Imiquimod 3.75%. In the present study, however, despite the evidence of clinical response to treatment, we did not find significant differences for O 2 Hb and HHb signals in the two periods.…”
Section: Discussionsupporting
confidence: 61%
“…Its ingredients, in fact, acts by repairing the UV-induced DNA damage and reducing the oxidative stress provoked by the photo exposure, but have only a moderate anti-inflammatory action and do not significantly modify the vascularization of the treated areas (22,23,36). The absence of statistical significance could also be due to the relative scarceness of the sample monitored by NIRS, compared to the study previously conducted (21), or to a different severity and extent of the lesions assessed. Unfortunately, the studies are not easily comparable on this point, since the evaluation of the extension was previously carried out in agreement with the grading proposed by Olsen (37) and not through the AKASI score.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation